Physiopathology Of Toxemias Of Pregnancy - Assali, N. (2015)
The present discussion will be limited to acute toxemia of pregnancy in its stages known as preeclampsia and eclampsia. This limitation excludes conditions which might coincide with pregnancy such as chronic hypertensive, cardiovascular or renal diseases. lt should be realized, however, that acute toxemia might become superimposed on anyone of these conditions and its recognition as such might present certain difficulties.